Payment for Ecosystem Services -: A strategy for environmental conservation in productive agricultural regions of Brazil? (Sustainability in Debate, 2013)
The world population is expected to reach 9 billion by 2050, which will put greaterpressure on natural resources to ensure the nutritional requirements and well-beingfor such a large population. Enormous investments in agricultural research, health,energy sources, material technologies, policies for poverty reduction and strategiesfor sustainable development must be made to meet this scenario. Actions to conservenatural resources and ecosystem services are implicit in sustainabledevelopment strategies. An increase in the number of public policies beingimplemented, their results, ongoing projects and research related to environmentalconservation are being observed and attest to their current and future relevance.